Determinants of Smoking Cessation Efforts Among Adolescent Males Using the Health Belief Model (HBM) Approach in Pidie - Miftahul Jannah; Said Usman; Ismail Ismail; Irwan Saputra; M. Marthoenis (International Journal of Public Health, 2025)
Background: Smoking among adolescents in Pidie, Aceh, is a growing public health concern, marked by increasing prevalence and significant household expenditure despite known health risks. This behavior persists due to cultural and social influences and a lack of motivation to quit, with adolescents' perceptions of risk, though crucial, not fully understood. Method : This analytical cross-sectional survey of 303 male high school students in Pidie used Partial Least Squares (PLS) to examine the relationship between Health Belief Model (HBM) factors and smoking cessation efforts. Result : The findings revealed that perceived barriers (t-statistic = 4.284 > t-table = 1.96), perceived susceptibility (t-statistic = 2.050 > t-table = 1.96), and perceived benefits (t-statistic = 4.082 > t-table = 1.96) had a direct significant relationship with cessation attempts, while perceived severity did not. Conclution: This study concluded that perceived barriers actually motivate quitting, with negative experiences like health problems for themselves or family acting as triggers. Therefore, understanding both the benefits and barriers is key to increasing smoking cessation motivation among adolescent males.